Implementation of the Lora System for Temperature and Humidity Monitoring in POLBAN Classrooms - Arman, Muhammad; Falahuddin, Muhammad Anda; Susilawati (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2023)
The need for temperature and humidity monitoring in classrooms, is very important for the purpose of comfortable teaching and learning processes, especially after the Covid-19 pandemic conditions. At Politeknik Negeri Bandung (POLBAN), there are more than a hundred classrooms. The rooms are spread over several buildings; therefore, the process of monitoring temperature and humidity will be difficult if it is done using a cable (wireline). In this study, a temperature and humidity monitoring system for classrooms at POLBAN will be made using LoRa wireless architecture. In several classrooms, temperature and humidity sensors will be installed combined with a LoRa sending system. There are conditioned room and unconditioned room. On the monitoring center, a LoRa receiver system is also installed. Data from each classroom, will wirelessly be sent to the monitoring center, for further processing. In the implementation stage, one gateway, 4 endnotes with DHT11 sensor are used. Testing process is carried out by verifying and monitoring performance in 4 classrooms and in open spaces. Results of verifying show a difference of 2℃ and 1% of the RH value with a reference measuring instrument. There is no difference in temperature and RH values at the endnode and gateway.